MANAJEMEN ASSET WAQF PADA PERGURUAN TINGGI : STUDI PADA UNISSULA - Gustina Gustina; Hidayatul Ihsan (Politeknik Negeri Padang, 2018)
Since the time of the Prophet Muhammad, waqaf has been used as a support and enhancing means of community welfare. Many sectors have been improved and updated by waqaf such as religious facilities, hospitals, schools / education, economic facilities and others. The waqf study in higher education is still relatively rare for Indonesia. But in the world, there are many universities that carrying the principle of waqf as its basis, such as Al-Azhar University Cairo, University of Cordoba Spain and so on. This study aims to explore the application of waqf for higher education in terms of management and economics. The methods used are interviews, observation and review of literature on books, manuscripts and publications. The researchers choose UNISSULA, which is managed by the Sultan Agung Waqf Board Foundation (YBWSA) as a case. The study shows that continuity of the using waqf in the community is determined by the management of waqf carried out by the manager (Nazhir) and the foundation of the waqf mandate holder.